Brand Loyalty in the Coffee Business: Economic Analysis of Brand Image, Product Quality, and Price - Raja, Jesika Lumban; Kusuma, Yanda Bara (International Journal of Economics Development Research (IJEDR), 2025)
This research aims to analyze and understand the influence of brand image, product quality, and price, both partially and simultaneously, on brand loyalty for Starbucks beverage products in Surabaya. The research population consists of Starbucks customers in Surabaya who have made at least two purchases. Using a purposive sampling technique, a total of 97 respondents were selected, with data collected through a Google Form questionnaire. Data analysis was conducted using multiple linear regression. The results indicate that brand image, product quality, and price simultaneously have a significant effect on brand loyalty. However, partially, brand image does not significantly influence brand loyalty, whereas product quality and price have a significant positive effect on brand loyalty.